Probation staff supervision: Valuing ‘me time’ within congested spaces - Coley, David (Probation journal, 2020)
Probation staff supervision is an established professional practice tool, documented historically through the lens of the Probation Journal. This article charts Journal discussions surrounding staff supervision and places them alongside a recent research study examining current practice. Study findings indicate that staff value dedicated time and space for structured supervision that contains significant elements of a more clinical approach. Nevertheless, supervision functions within congested spaces in which managerial aspects of staff engagement encroach. Finding an accommodation between differing approaches appears challenging. More broadly, competing views resound within a landscape of looming professional registration and associated requirements of continuous professional development.